Human genetic studies in areas of high natural radiation. VIII. Genetic load not related to radiation - Freire Maia, A.; Krieger, H. (My University, 1975)
The genetic load disclosed by inbreeding has been analyzed in a multiple regression model for a population involving several localities in the state of Espirito Santo, Brazil. The inbreeding load has been estimated for the number of pregnancies, abortions, stillbirths, children born alive, anomalies in general, sex ratio, infant mortality, post infant mortality, and sterility and infertility of the couple. There was no evidence of either maternal or paternal inbreeding effects on the variables analyzed. The effect of inbreeding of the zygote was significant only for anomalies in general (B = 2.29 ± 0.45) and infant mortality (B = 3.19 ± 1.39). The latter results must be accepted with caution because of the many environmental causes affecting infant mortality. The B/A ratio suggested a predominantly mutational load for anomalies in general (B/A = 25), but with respect to infant mortality (B/A = 6), the ratio is regarded as an underestimate because of the environmental contribution to A and therefore not supportive of the segregational interpretation.